The Influence of Information Technology and Management Control Systems on Employee Performance - Gun Gunawan Rachman; Sita Nuraeni (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
This study aims to determine the influence of information technology and management control systems on employee performance at PT. Adira Dinamika Multifinance Tbk Baleendah Branch. The study was conducted on the employees of PT. Adira Dinamika Multifinance Tbk Baleendah Branch in the marketing division of 33 people. The research data is primary data and the analytical method used is descriptive verification method with quantitative approach and hypothesis testing and through data collection techniques with questionnaires. The statistical test tool used in this study is the Structural Equation Model (SEM) with Partial Least Square (PLS) estimation. The results of this study indicate that: 1) Information technology significantly influences employee performance 2) Management control system significantly influences employee performance